Psychasthenia and its relationship to some physical performance variables among female students of College of Physical Education (College of Basic Education Research Journal, 2025)
Study aimed to measure  level of feeling  psychasthenia by female students of College of Physical Education and Sport Sciences / University of Al-Hamdaniya , to identify  relationship of psychological weakness and its dimensions on some variables of physical performance among them,  Research sample was  (32) female students from College of Physical Education and Sport Sciences at Al-Hamdaniya University, selected using comprehensive inventory method, Researchers used  psychological weakness scale prepared by (Faraj, 2023),  with (31) paragraphs, in addition to physical tests, personal interviews, and questionnaires as means of collecting data to achieve objectives of research, as for statistical methods,  SPSS statistical program was used to extract results, which were: Female students of College of Physical Education and Sport Sciences  characterized by their feeling of psychological weakness, there was no clear role for psychological weakness on physical performance among female students of the College of Physical Education and Sport Sciences.
Keywords: psychological weakness; physical performance variables